Case report: A case of proliferative glomerulonephritis with monoclonal kappa-light chain deposits treated with daratumumab combination therapy - Wang, Jue; Lv, Jun-Ting; Xiao, Dan; Liu, Jia; Du, Jun; Zhong, Lu (Frontiers in Medicine, 2024)
Proliferative glomerulonephritis with monoclonal immunoglobulin deposits (PGNMID) is a chronic glomerular disease caused by monoclonal gammopathy. IgG (mainly IgG3) is the most commonly involved isotype of PGNMID. Here we illustrated a novel medication regimen fo the rare variant of PGNMID with deposition of monoclonal immunoglobulin light chain only (PGNMID-LC). Daratumumab has been proved effective in the treatment of plasma cell myeloma while its effect for PGNMID-LC has rarely been reported.A Daratumumab combination therapy (D-VCd regimen, specifically are Daratumumab + Dexamethasone + Bortezomib + Cyclophosphamide) was adopted to treat a patient diagnosed with PGNMID-LC.The utility of D-VCd regimen showed a favorable effect in this patient. After the fixed course, his clinical symptom, laboratory parameters, neoplastic plasma cells clonity all restored to normal range, and no obvious disease progression was observed throughout the treatment. After a follow up of 14 months, no significant renal or hematological disease progression has been observed.This case underscores the utility of D-VCd regimen in treatment of PGNMID-LC, and it's inferred that Daratumumab regimen has clinical effects in the disease primarily through targeting tumor clonity. However, data on the use of Daratumumab (either in monotherapy or in combination) in clinical trials of PGNMID-LC is currently so limited that that more experiments are needed to support the inference.